Observation of Village Cleanup Activities to Prevent Dengue Fever - Y. Edo Budi Prasetyo; Ridwan Arifin (Jurnal Abdimas Imigrasi, 2020)
The purpose of implementing village clean-up activities by the Immigration Polytechnic Cadets together with the Class III Non TPI Kediri Immigration Office in this activity is a form of concern for the surrounding environment, especially the Klampitan Village community, Kediri City. This activity was carried out in the context of the 2019 Level Three Cadets Real Work Lecture in the form of community service activities. This activity is one form of social responsibility for the Immigration Polytechnic Cadets as part of community service by the Immigration Polytechnic as mandated in the Tri Dharma of Higher Education.